The long-term impact of increased red blood cell distribution width detected during hospitalization for heart failure - Mayer, Otto; Bruthans, Jan; Jirák, Josef; Filipovský, Jan (Biomarkers in medicine, 2024)
Aim: We determined the long-term role of increased RDW (red blood cell distribution width) detected during cardiac decompensation.Methods: We followed 3697 patients [mean age 71.4 years (±SD 10.1), 59.1% males] hospitalized for acute heart failure (HF) and assessed the five-year all-cause mortality risk associated with tertiles of RDW.Results: Patients with RDW in the top tertile showed roughly twofold higher 5-year mortality risk than those in the bottom tertile. The association remained significant not only after adjustments for potential covariates but even if we excluded patients who deceased during the first year of follow-up [HRR 1.76 (95% CIs:1.42-2.18), p < 0.0001].Conclusion: The high degree of anisocytosis represents an independent predictor of poor prognosis in HF patients, even long-term after an acute manifestation.
Keywords: Prognosis; senioři nad 80 let; Humans; erytrocyty; následné studie; lidé středního věku; Middle Aged; Aged, 80 and over; prognóza; Follow-Up Studies; Erythrocyte Indices; mužské pohlaví; hospitalizace; srdeční selhání; erytrocytární znaky; Hospitalization; ženské pohlaví; lidé; Erythrocytes; Heart Failure; Aged; senioři; Male; Female